Right-Left Symmetry in Shoot and Flowers of Tribulus Cissoides - Tennakone, K. (My University, 1985)
Tribulus Cissoides has oppositely placed large and small paripinate compound leaves at the nodes alternating between right and left hand sides. The flowers arising at the axils of small leaves have clockwise(right-handed)or anticlockwise (left-handed)imbricated petals depending on whether they are on the right or the left hand sides of the stem. Thus Geometrically, the Structure at each node is the mirror image of the one above or below. It is found that the flower differentiation process favours 'left handness,' for about 53% of the flowers orginate in the left-handed leaf axils and approximately the same percentage of secondary shoots orginate in the right-handed leaf axils.